Factors associated with increased symptoms of depression among South Africans living with chronic illness - Haripersad, Dipika (Department of Psychiatry and Mental Health, 2026)
Background Depression is one of the leading causes of disability in developing countries. People living with chronic illness are more vulnerable to developing depression. Although this connection is well established, the factors associated with severe depressive symptoms in people living with a chronic illness are poorly understood. South Africa has a high prevalence of depression and of chronic illness, particularly HIV and Diabetes, yet the literature is sparse regarding depressive symptoms, and particularly severe depression symptoms, in this group. To address this gap, this study aims to investigate the risk factors associated with severe depression symptoms among South Africans living with a chronic illness. Methods A secondary data analysis was done using a quantitative cross sectional design. De-identified data was obtained from the parent study (Project Mind), utilising the baseline data from this cluster randomised controlled trial of a brief intervention for depression and risky alcohol use in primary care amongst patients living with HIV or diabetes mellitus. Cases included for this study were those who were at risk for depression at the baseline interview. Depression was measured using the 20-item Centre for Epidemiological Studies Depression Scale (CES-D) tool and those scoring 16 or above were identified as being at risk for depression. Factors associated with severe symptoms of depression were explored separately in the diabetes and HIV groups using unadjusted and adjusted logistic regression models. The dependent variable was severe depression symptoms (a binary categorical variable), indicated by a CES-D score of 29 or more. Independent variables included sociodemographic, chronic illness diagnosis, biological markers of chronic illness control, alcohol and drug use, adherence and numbers of different types of traumatic experiences. Results The study sample comprised mainly female participants and ages ranged from 19 to 88 years. The majority were unemployed (57%), did not complete high school (67%) and reported earning less than R2000 per month (76%). Over 70% of the 1 117 participants scored above threshold for severe depression symptoms in this study and of the 525 participants who reported using alcohol, 27% were using alcohol at high risk levels. In the adjusted model for the HIV group, female participants (OR 1.871, CI 1.179 - 2.969), those using alcohol at high risk levels (OR 1.627, 1.038 - 2.551) and participants reporting ten or more trauma types (OR 2.191, 1.218 - 3.942) were significantly more likely to report increased symptoms of depression compared to other participants. In the diabetes group, only those who had experienced 7-9 (OR 2.500; CI 1.423 - 4.392) and 10 or more trauma types (OR 3.275; CI 1.598 - 6.710) were significantly associated with severe depression symptoms. Conclusion Findings from this study have provided insight into characteristics of patients living with a chronic illness who may be at risk for severe depression. Income support, risky alcohol use or traumatic experiences should be explored as targets for intervention in this vulnerable group. Ethical Considerations All data for this study was obtained from “Project Mind” (Pan African Clinical Trial registry – trial registration number – ACT201610001825403). The This study was submitted to the Human Research Ethics Committee at the Faculty of Health Sciences, University of Cape Town, South Africa. HREC Ref: 774/2021. Ethics approval was granted on 3 December 2021. Non-essential identifying information was used in the data collection and storage. Secondary data will be stored on locked and secure computer. No further recruitment was performed.